The dream keeper and other poems - Hughes, Langston, 1902-1967.; Pinkney, J. Brian (New York : Knopf, 1996)
A collection of sixty-six poems, selected by the author for young readers, including lyrical poems, songs, and blues, many exploring the black experience.
The Dream Keeper -- The Dream Keeper -- Winter Moon -- Dreams -- Winter Sweetness -- April Rain Song -- Joy -- After Many Springs -- Quiet Girl -- Fairies -- Autumn Thought -- Poem -- Sea Charm -- Sea Charm -- Water-Front Streets -- Long Trip -- Death of an Old Seaman -- Seascape -- Sailor -- Irish Wake -- Beggar Boy -- Parisian Beggar Woman -- Mexican Market Woman -- Sea Calm -- Dressed Up -- A Note on Blues -- Dressed Up -- Bound No'th Blues -- Song -- The Weary Blues -- Negro Dancers -- Song for a Banjo Dance -- Reasons Why -- Minstrel Man -- Po' Boy Blues -- When Sue Wears Red -- A Black Pierrot -- Wide River -- Passing Love -- Homesick Blues -- Night and Morn -- Feet o'Jesus -- Feet o'Jesus -- Baby -- Ma Lord -- Judgment Day -- Lullaby -- Prayer -- Sinner -- Prayer Meeting -- Walkers with the Dawn -- Walkers with the Dawn -- Dream Variation -- The Negro -- My People -- Sun Song -- The Negro Speaks of Rivers -- I, Too -- Mother to Son -- Youth -- Alabama Earth -- Lincoln Monument: Washington -- Aunt Sue's Stories -- As I Grew Older -- African Dance -- Additional Poems -- Snail -- Stars -- Dream Dust -- Color -- Daybreak in Alabama -- Merry-Go-Round -- In Time of Silver Rain.
"Including seven additional poems."
Keywords: Children's poetry, American; African Americans -- Juvenile poetry; African Americans -- Poetry; American poetry -- African American authors